DYNAMICS OF POLYSTYRENE MICROSPHERE LINKING TO Î»-PHAGE DNA MOLECULE IN OPTICAL TWEEZERS USING PULSED GAUSSIAN LASER BEAM - Trung, Thai Dinh (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
The trapping process of the biological micro-particle in the tweezers using CW laser beam has been investigated in series of our works. In the CW regime, the dynamics of polystyrene microsphere linking to Î»-phage DNA molecule depending on the optical force, Brown force and its elastic force are simulated and discussed. In this paper we present the finite difference Langevin equation (FDLE) describing the dynamics of trapped bead linking to DNA molecules in an optical tweezers. Using FDLE the dynamics, i.e., the position-time characteristics of polystyrene microsphere linking to Î»-phage DNA molecule are simulated in the pulse regime. The obtained results show that all principle parameters as the peak intensity, beam waist radius, and duration of pulsed Gaussian laser beam, well as the setting-up position of DNA molecule influence on the dynamics, especially on the pulling and aœstability times of trapped bead. The conditions for Î» -phage DNA molecule in stretching state are discussed for experimence.